2016
DOI: 10.1038/srep25293
|View full text |Cite
|
Sign up to set email alerts
|

Employing Synergetic Effect of Doping and Thin Film Coating to Boost the Performance of Lithium-Ion Battery Cathode Particles

Abstract: Atomic layer deposition (ALD) has evolved as an important technique to coat conformal protective thin films on cathode and anode particles of lithium ion batteries to enhance their electrochemical performance. Coating a conformal, conductive and optimal ultrathin film on cathode particles has significantly increased the capacity retention and cycle life as demonstrated in our previous work. In this work, we have unearthed the synergetic effect of electrochemically active iron oxide films coating and partial do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
(45 reference statements)
1
28
0
Order By: Relevance
“…Metal ions could enter the lattice structure of cathode particles during ALD processes. 123,124 The ALD deposition process may begin at the structural defects, aer the defects were saturated, the ions began to participate in the formation of oxide lms on the surface of the cathode particle. Patel et al reported that ALD Fe 2 O 3 coating provided signicant performance improvement of the LMNO cathode.…”
Section: Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ions could enter the lattice structure of cathode particles during ALD processes. 123,124 The ALD deposition process may begin at the structural defects, aer the defects were saturated, the ions began to participate in the formation of oxide lms on the surface of the cathode particle. Patel et al reported that ALD Fe 2 O 3 coating provided signicant performance improvement of the LMNO cathode.…”
Section: Electrode Materialsmentioning
confidence: 99%
“…Patel et al reported that ALD Fe 2 O 3 coating provided significant performance improvement of the LMNO cathode. 123 Compared with other doping methods, slight doping using ALD would enhance the cycle stability of LIB cathode, while excessive doping may cause distorted lattice structure or impeded Li + diffusion channels, which could reduce the capacity.…”
Section: Applicationsmentioning
confidence: 99%
“…Doping is an effective approach to stabilize structure and improve cycle performance. Bulk doping during materials production aim for suppressing the phase transition [91,92] on cathodes, but the excessive and unbridled doping will hinder the lithium ions diffusion channels in the bulk structure, resulting in active capacity loss [39] at first cycle [93]. Considering the fact that the side reactions primarily happen on the surface of cathodes due to the imbalanced lithium ions movability on the boundary particularly at high current densities [45], restricting the controllable doping modification within only the surface turns out to be a feasible and promising approach.…”
Section: Stabilizing Cathode Structurementioning
confidence: 99%
“…Up to now, most of the reported work focuses on the performance of the battery rather than the interaction between the ALD materials with the other components of the battery during charge/discharge. For instance, Patel et al studied the ALD Fe 3 O 4 coating on the LiMn 1.5 Ni 0.5 O 4 cathode . They pointed out that initially the Fe penetrated into the LiMn 1.5 Ni 0.5 O 4 structure and acted as a dopant.…”
Section: Lithium‐ion Batteriesmentioning
confidence: 99%